Louisa : the life of Louisa May Alcott - McDonough, Yona Zeldis; Andersen, Bethanne, 1954- (New York : Henry Holt and Co., 2009)
Louisa came from a family that was poor but freethinking, and she started teaching when she was only seventeen years old. But writing was her passion. This biography captures the life of a compassionate woman who left an indelible mark on literature for all ages.
"Christy Ottaviano Books."
Includes bibliographical references.
A Junior Library Guild selection
Keywords: Alcott, Louisa May, -- 1832-1888 -- Juvenile literature; Alcott, Louisa May, -- 1832-1888.; Authors, American -- 19th century -- Biography -- Juvenile literature; Authors, American -- 19th century -- Biography